Evaluation of English for Palestine Textbooks and English Language Examination in Light of Common European Framework of References for Languages (CEFRL) - Khora, Haneen Mohammed (Journal of Educational and Psychological Sciences, 2021)
This study aimed at identifying the degree of alignment between English for Palestine textbook tasks, its intended objectives, and teachers’ exams in the light of (CEFRL).To achieve this purpose and to answer the research questions, the researcher adopted a descriptive analytical method and chose a sample consisted of 10th grade English for Palestine textbook. The sample consists of 55 midterm and final exams for 10th grade. A sample of 10 English language teachers was selected randomly to answer the structured interview. The researcher utilized two main instruments; a framework for the analysis of the tasks included in 10th grade English for Palestine textbook, and a structured interview. It has been applied to monitor the recurrence of task skills and objectives, and then calculates the alignment between the two elements using Porter’s alignment Index.To determine the reliability of the instruments, Holsti's Equation was used. Frequencies and Porter Alignment Index were used to analyze the collected data. The major findings of the study revealed that most textbook tasks were A2 level; the highest tasks were reading and writing tasks. Teachers’ exams were at the A2 level with high concentration on reading and writing skills. Results showed that most of exams excluded speaking and listening. There is a low alignment between 10th grade textbook tasks and the objectives intended to be achieved by the end of 10th grade. Moreover, there is moderate alignment between textbook tasks and exams. The application level of Bloom’s taxonomy has the highest percentage; however, the evaluation level does not achieve any score. Based on the previous findings, the study recommends that textbook designers should reconsider the nature of the tasks in the English language textbook to align them with the objectives of the textbook. They also need to design training courses for teachers on the development of exams so that they are aligned with the Common European Framework of References for Languages (CEFRL), and achieve a stated balanced distribution for each skill.
Keywords: alignment; CEFRL; English tasks